Upaya Vibes Media Group Membangun Brand Awareness dengan Menentukan Layanan Unggulan menggunakan AHP - Benediktus Johan Ekatama (Jurnal Titra, 2022)
Vibes Media Group is a promotion service company that wants to increase Brand Awareness by specializing one of it’s service. The company provides several services provided such as branding agencies, Instagram management, YouTube management, event documentation, on-demand filmmaking, and website creation. This research is intended to determine which services will be the specialty of Vibes Media Group in order to increase brand awareness. The model calculation is done by taking questionnaire data from the Vibes Media Group team. Decision-making is done using the Analytical Hierarchy Process method with the help of super decisions application. The Analytical Hierarchy Process is a method for making decisions with many supporting criteria. Several criteria are compared with each other based on their level of importance. The results of the analysis show that Branding Agency is the right choice to specialize as a Vibes Media Group service by considering Exposure, Fee Amount, Networking Potential, Contract Period, and Work Complexity.